2018
DOI: 10.1074/jbc.ra118.001730
|View full text |Cite
|
Sign up to set email alerts
|

Histone demethylase JMJD1A promotes colorectal cancer growth and metastasis by enhancing Wnt/β-catenin signaling

Abstract: The abbreviations used are: JMJD1A, jumonji domain containing 1A; CRC, colorectal cancer; PCNA, proliferating cell nuclear antigen; MMP9, matrix metallopeptidase 9; IP, immunoprecipitation; ChIP, chromatin immunoprecipitation; H3K9, histone-3 lysine-9; GEO, Gene Expression Omnibus. Key words: histone demethylase; JMJD1A; epigenetics; colorectal cancer; proliferation; metastasis; Wnt/β-catenin signaling ABSTRACTThe histone demethylase Jumonji domain containing 1A (JMJD1A) is overexpressed in multiple tumors and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 33 publications
2
53
0
Order By: Relevance
“…Many reports showed that JMJD1A affects cancer metastasis (22)(23)(24)(25)(26). However, the mechanism of the histone demethylase JMJD1A in prostate cancer metastasis is poorly understood.…”
Section: Jmjd1a Impedes Prostate Cancer Progression Through a Key Tramentioning
confidence: 99%
“…Many reports showed that JMJD1A affects cancer metastasis (22)(23)(24)(25)(26). However, the mechanism of the histone demethylase JMJD1A in prostate cancer metastasis is poorly understood.…”
Section: Jmjd1a Impedes Prostate Cancer Progression Through a Key Tramentioning
confidence: 99%
“…In prostate cancer, FZD8 integrates with Wnt11 and TGF‐β signaling to increase EMT and further cellular migration . Epigenetic modulation of canonical Wnt signaling by the histone H3K9 demethylase JMJD1A results in increased cell scattering and metastasis in CRC . Furthermore, during lung adenocarcinoma progression, activation of canonical Wnt/TCF signaling through LEF1 and HOXB9 has been reported as a determinant of bone and brain metastasis …”
Section: Rationale For Targeting Wnt Signalingmentioning
confidence: 99%
“…KDM3A has been reported to activate the Wnt signaling pathway in colorectal cancer to promote cell growth and metastasis [30]. Therefore, we detected the expression of β-catenin, c-Myc, and cyclinD1, Wntrelated proteins, by Western blotting.…”
Section: Resultsmentioning
confidence: 96%